Effect of Display Polarity on Amplitude of Accommodation and Visual Fatigue - Muhamad, Nurulain; Moktaeffendi, Nurul Hanna; Azni, Nur Syuhadah (Environment-Behaviour Proceedings Journal, 2023)
This study aimed to assess the changes in the amplitude of accommodation under different display polarities and ascertain the effect of display polarities on visual fatigue. Thirty subjects randomly underwent a reading task for 30 minutes with both positive and negative display polarities. The amplitude of accommodation was measured, and subjects were required to complete a subjective symptoms questionnaire; both before and after the reading task. The amplitude of accommodation and visual fatigue symptoms were significantly reduced after the reading task, with both display polarities.